The selective 5-HT1A receptor agonist, NLX-112, exerts anti-dyskinetic effects in MPTP-treated macaques. (September 2020) - Depoortere, R.; Johnston, T.H.; Fox, S.H.; Brotchie, J.M.; Newman-Tancredi, A.
Abstract: Background: Long-term treatment of Parkinson's disease (PD) with l -DOPA typically leads to development of l -DOPA induced dyskinesia (LID). Amantadine, an NMDA antagonist, attenuates LID, but with limited efficacy and considerable side-effects. NLX-112 (also known as befiradol or F13640), a highly selective and efficacious 5-HT1A receptor agonist, reduced LID when tested in rodent and marmoset models of PD. Methods: The effects of NLX-112 (0.03, 0.1 and 0.3 mg/kg PO) on established LID evoked by acute challenge with l -DOPA (27.5 ± 3.8 mg/kg PO) were assessed in MPTP-treated cynomolgus macaques. Amantadine (10 mg/kg PO) was tested as a positive control. Plasma exposure of NLX-112 (0.1 mg/kg PO) was determined. Results: NLX-112 significantly and dose-dependently reduced median LID levels by up to 96% during the first hour post-administration (0.3 mg/kg). Moreover, NLX-112 reduced the duration of 'bad on-time' associated with disabling LID by up to 48% (0.3 mg/kg). In contrast, NLX-112 had negligible impact on the anti-parkinsonian benefit of l -DOPA. NLX-112 exposure peaked at ~50 ng/ml at 30 min post-administration but decreased to ~15 ng/ml at 2h. Amantadine reduced by 42% 'bad on-time' associated with l -DOPA, thereby validating the model. Conclusion: These data show that, in MPTP-lesioned cynomolgus macaques, NLX-112 exerts robust anti-dyskinetic effects, without reducing the anti-parkinsonian benefit of l -DOPA. These observations complement previous findings and suggest that selective and high efficacy activation of 5-HT1A receptors by NLX-112 may constitute a promising approach to combat LID in PD, providing an alternative for patients in whom amantadine is poorly tolerated or without useful effect. Highlights: NLX-112 is an exceptionally selective, potent, efficacious 5-HT1A receptor agonist. In MPTP-lesioned cynomolgus macaques, NLX-112 exerts robust anti-dyskinetic effects. NLX-112 reduced l -DOPA-induced dyskinesia (LID) by up to 96% at early time points. NLX-112 did not impact the anti-parkinsonian benefit of l -DOPA. NLX-112 did not elicit unusual behaviors in macaque, unlike previously in marmoset.